2019
DOI: 10.1055/a-0956-1889
|View full text |Cite
|
Sign up to set email alerts
|

Key performance measures for colonoscopy in the Polish Colonoscopy Screening Program

Abstract: Background The European Society of Gastrointestinal Endoscopy (ESGE) has published guidelines on key performance measures for colonoscopy. We analyzed whether those standards were met in the Polish Colonoscopy Screening Program (PCSP) and whether the monitoring was feasible. Methods We analyzed database records for 43 277 PCSP participants (25 PCSP centers) for the years 2014 – 2015. We used the guideline definitions to calculate values for all key performance measures and compared these with the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…21 Possible reasons for these variations in bowel preparation assessment include endoscopist skill level differences, heavy work load, inattention, and emotional factors. 13,14 Assistance from nurses when making assessments could help bias address these variations. However, a human rater cannot compensate for the inherent defects of subjective factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Possible reasons for these variations in bowel preparation assessment include endoscopist skill level differences, heavy work load, inattention, and emotional factors. 13,14 Assistance from nurses when making assessments could help bias address these variations. However, a human rater cannot compensate for the inherent defects of subjective factors.…”
Section: Discussionmentioning
confidence: 99%
“…12 In clinical practice, inaccurate and missing bowel preparation recording could be attributed to multiple factors such as work load, shortage of supervision, and lacking practical tools. 13,14 Although studies have tried to introduce nurse raters to improve the quality of bowel assessment and reduce endoscopists' work load and bias introduced by endoscopists' assessments, the nurse raters cannot avoid the inherent defect of human rating. 15 Establishing practical and feasible methods to improve bowel preparation assessment in daily endoscopy is essential.…”
Section: Introductionmentioning
confidence: 99%
“…The number of assessed indicators could be increased over time as registry implementation progresses. This is supported by the study of Bugajski et al, 10 which showed that collecting data on all 7 quality indicators endorsed by the European Society of Gastrointestinal Endoscopy was feasible 10 years after the introduction of quality assurance programs within the Polish Colonoscopy Screening Program.…”
mentioning
confidence: 72%
“…A study by Greene et al, 9 who reviewed impediments encountered in matching colonoscopic and pathologic data in a New Hampshire population-based registry, showed that only 50% of polyps removed during screening and diagnostic colonoscopies were correctly matched with pathologic data with no assumption or discrepancy. Although the DGEA could calculate ADR for only 54% of the participating centers, and some other European screening colonoscopy registries showed more complete data, [10][11][12] the former used an automated system and the latter used manual data entry. Because manual matching of endoscopic and pathologic data is one of the major impediments to widespread and accurate measurement of ADR, 13 the introduction of an automated data extraction and analysis tool is a major achievement.…”
mentioning
confidence: 99%
“…Wallace et al demonstrated a significant improvement in ADR with multiple educational and system interventions, such as providing endoscopist report cards, education on how to achieve higher ADR and colon inspection techniques, and posting deidentified ADRs of physicians in the endoscopy unit (ADR 36%-47%; P , 0.001); these improvements were sustained 6 months later (83,84). Others have also demonstrated favorable improvements in polyp detection, adenoma detection, and WT with education and feedback that is sustained one year or longer (45,(85)(86)(87). For low performers, we recommend evaluation of withdrawal technique with emphasis on cleaning, suctioning, looking behind folds, and going back and forth during withdrawal.…”
Section: Educational and Multistep Interventionsmentioning
confidence: 99%